A construção identitária da RBS TV na campanha autopromocional comemorativa de seus 50 anos. - Ternus, Carline (2014)
The present dissertation has the purpose of investigating how, as an affiliate, a broadcast station builds its own identity, distinguish its production from that one made by the network head and, finally, the manner how configures its image, while reinforcing the mother network s identity and, along with it, realizes its own productions in a coherent way. For this, the present work analyses, based on Greimasian discursive semiotics, 13 pieces of the RBS TV s 50th anniversary self-promotional campaign, seeking to verify solutions found by them to respond the challenge of articulate different interests that, commonly, work in opposite directions. Therefore, the main objective of this investigation is to comprehend how the identity construction and the image and brand projection are made during the period of an assumed self-promotional action, verifying which are the discursive procedures adopted by the aforesaid campaign, through the self-talking production, and which forms of expression actualize this strategies of identity construction in the specific case of an affiliate broadcast station. The research, structured in nine sections, after a theoretical foundation about the promotional field and a brief exhibition of the appropriate discursive semiotics concepts that support the methodology used for the selected self-promotional pieces analysis, turns out to the corpus study, considering, as a point of view, its communicative/enunciative context and inter and extra-textual relations.